International interlaboratory validation of a nested PCR for molecular detection of Babesia bovis and Babesia bigemina, causative agents of bovine babesiosis - Ganzinelli, Sabrina Belen; Byaruhanga, Charles; Primo, María Evangelina; Lukanji, Zinathi; Sibeko, Kgomotso; Matjila, Tshepo; Neves, Luis; Benitez, Daniel Francisco; Enkhbaatar, Batmagnai; Nugraha, Arifin Budiman; Igarashi, Ikuo; Florin-Christensen, Mónica; et al. (Elsevier, 2022)
Babesia bovis and B. bigemina are tick-transmitted parasites causing bovine babesiosis, characterized by significant morbidity and mortality leading to economic losses to the livestock industry in tropical and subtropical regions worldwide. Animals that recover from acute infection remain carriers with low parasitemia acting as a source of transmission, and often escape detection. An improved diagnosis of a B. bovis and/or B. bigemina infection of carrier animals is enabled by the availability of detection methods with high sensitivity. To this end, two nested PCR assays targeting the cytochrome b (cytb) genes of B. bovis and B. bigemina (cytb-nPCR), have been recently developed and an increased sensitivity with respect to reference protocols has been shown (Romero-Salas et al., 2016). In this study, the specificity against a panel of hemoparasites that potentially co-occur with B. bovis and B. bigemina was demonstrated to ensure applicability of the cytb-nPCR assays in a wide range of regions where bovine babesiosis is endemic. Furthermore, we compared both reported cytb-nPCR assays with reference nPCR and qPCR protocols for (i) their capability to detect carrier animals in the field, and (ii) their reproducibility when performed in different laboratories by independent operators. We show that, in a panel of bovine field samples (n = 100), the cytb-nPCR assays detected a considerably higher number of 25% B. bovis and 61% B. bigemina-positive animals compared to 7% and 20% B. bovis and 55% and 49% B. bigemina-positive animals when tested by reference nPCR and qPCR protocols, respectively. Cytb-nPCRs were also found superior in the detection of carrier animals when field samples from Africa were analyzed. In addition, both the B. bovis and B. bigemina cytb-nPCR assays were independently validated in a single blinded study in three laboratories. Importantly, no significant differences in the number/percentage of infected animals was observed using cytb-nPCR assays. In summary, the cytb-nPCR assays detected a considerably higher number of chronically infected B. bovis and B. bigemina carrier animals compared to reference nPCR and qPCR protocols, when applied in different epidemiological field situations. Furthermore, a high reproducibility between laboratories could be demonstrated.